TIMEG: Development and Evaluation of an Inspection Checklist Tool for Mobile Educational Games - Frazão, Kastney; Pessoa, Alexandre; Paiva, Anselmo; Viana, Davi; Rivero, Luis (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
The software inspection process allows identifying defects during the development cycle. In the context of mobile serious games, specific inspection checklists can be employed to guarantee their quality. However, there are few tools to support the use of these checklists and the existing ones are generic and not specific for the evaluation of digital educational games for mobile devices. To assist software engineers in the evaluation of this type of games, an open-source desktop tool was developed in C#, called TIMEG (Tool for Checklist Inspection of Mobile Educational Games). TIMEG allows to: (1) embed inspection checklists; (2) point out defects based on the items in the checklists; (3) generate inspection reports; and if the game is already available in the Google Play store, (4) present information about the users’ opinions. The tool was evaluated from the point of view of inexperienced software engineers when applied for evaluating a mobile serious game; and through the answers to a questionnaire. The results indicate that the tool was perceived as useful and easy to use, in addition to identifying opportunities for improvement in the tool’s interface and usability, as well as improvements in the presentation of relevant information in the defect reports. Link para Vídeo: Clique Aqui